The contribution of neuroscience to forensic explanation - Ward, Tony (Psychology, crime & law, 2018)
In light of the growing interest in forensic neuroscience, a pressing question concerns whether or not neurobiological evidence and explanations can make a useful contribution to understanding and managing crime. Here we argue that neuroscience methodologies, such as EEG and fMRI, can provide a valuable source of information about phenomena related to criminal behaviour, which complements traditional sources such as interviews and self-report scales. However, despite this optimistic message, there is good reason to be cautious in interpreting neurobiological data. It is tempting to see this type of evidence as somehow ‘privileged’ over other sources. However, elucidating the neurobiological mechanisms that support a behaviour does not tell us what led to that behaviour. Given how little we currently know about the relationship between neural activity and specific mental functions, we should be cautious about inferring psychological processes on the basis of brain activity measures alone. Finally, we should always keep in mind that every neuroscience study is predicated upon a psychological framework, and this framework affects all aspects of the project. Therefore, the evidence obtained from a neuroscience study is only ever as good as the psychological framework on which that study was founded.